The Chinese Christian Fighting for thr Ming Dynasty, the Story of an Embassy - Miazek-Męczyńska, Monika (My University, 2011)
This article was published in "About Books, Maps, Songs and Steles: the Wording and Teaching of the Christian Faith in China" edited by Dirk Van Overmeire and Pieter Ackerman, Leuven Chinese Studies XXI (2011), p. 34-50.
Keywords: Jesuits; Ming dynasty; Michał Boym SJ; mission in China; Jesuit missionaries